Multivariate discrimination among cryptic mites of the genus Androlaelaps (Acari: Mesostigmata: Laelapidae) parasitic of sympatric akodontine rodents (Cricetidae: Sigmodontinae) in northeastern Argentina: possible evidence of host switch followed by speciation, with the description of two new species - Lareschi, Marcela (2014)
Laelapids are among the most common ectoparasites of rodents. Currently, it is under discussion whether there is a single polixenous species that parasites a variety of hosts, or whether there are cryptic species highly host specific. Herein, multivariate morphometric analyses of crypticsympatric laelapids of the genus Androlaelaps allowed us to identify different species. These species are specific of their akodontine hosts, Akodon montensis and Thaptomys nigrita, in localities situated in northeastern Argentina. In addition, we analyzed similar laelapids associated with the akodontines Deltamys kempi and Akodon cursor. Using principle component analyses we differentiated four laelapid species, each one host specific, independent of sympatry of the hosts, and without geographical variation. From these four species, we described two new species (Androlaelaps navonae n. sp. and Androlaelaps wingei n. sp.). We determined the four species based on a range of variations in several characters, mainly size. These four laelapid species belong to the Androlaelaps rotundus species group, specific to akodontines. These species are very similar among them but differ from the remainder species of the group by their small size, distance between j6 setae similar to the distance between the z5 setae, strong ventral setae, opisthogaster with 13 pairs of strong setae (one close to the distal margin of epigynal shield), and anal shield wider than long. Further studies will elucidate whether they constitute a new laelapid genus. Phylogenetic and ecological factors influencing host-specificity are discussed, and we propose that host colonization could have taken place by host switching of a single laelapid species among rodent species, followed by speciation.